Golden Eagle (Aquila chrysaetos) genomics across Scandinavia : population structure and effects of marker selection - Näsman, Måns (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2018)
Rapid development in DNA-sequencing has led to increased use of single nucleotide polymorphisms (SNPs) as molecular markers in wildlife genetic studies. RAD-sequenced SNP-markers can produce large datasets that are successfully used in studies on animal population structure. The high number of markers does however create both possibility and need for deliberate marker selection. Removal of markers outside Hardy Weinberg Equilibrium (HWE) to avoid sequencing error, might exclude informative markers, and marker selection at different minor allele frequencies (MAF) can generate differences in population structure. In the present study SNP-markers are used to study basic biology in Scandinavian Golden eagles, and by searching for genetic structure among populations, addresses questions of natal philopatry and interspecific gene flow. Simultaneously, effects of marker selection on population structure are examined. 8710 SNPs from 96 Golden eagles were analysed for population genetic structure using principal component analysis (PCA). Marker selections were based on HWE and different windows of MAF. Results show genetic structure indicating limitations in gene flow between mainland Sweden and the island of Gotland. Gradual east-west structure was found in mid Sweden and Norway, possibly related to habitat type. Markers outside HWE were important in detecting population structure, and inclusion of these in the PCA outweighed any effect of possible sequencing error. Different MAF-windows mainly affected the degree of separation between genetic clusters, but weak indices of some structuring only visible at certain MAF-windows were also found. These results support previous findings on natal philopatry of golden eagles and question the use of only HWE to identify sequencing error.